Development Method of High CRI LED Lighting Reflecting the Spectral Ratio Characteristics of Natural Light by Wavelength Band - Seung-Taek Oh; Ji-Young Lee; Se-Hyun Lee; Jae-Hyun Lim (Advances in Technology Innovation, 2026)
Although natural light is the standard reference for color rendering evaluation, limited efforts have been made to develop a lighting system that achieves high color rendering while replicating the spectral characteristics of natural light. This paper proposes a method for developing LED lighting that mimics the spectral ratio characteristics of natural light and achieves high color rendering. Based on the analysis of measured natural light spectra, spectral ratio characteristics are derived according to changes in color temperature. Simulations are conducted by adding light sources with specific peak wavelengths (405 nm, 630 nm) to commercial LED lighting. Based on the simulation results, a development approach for natural light LED lighting with high color rendering is proposed. Experimental results demonstrate that a color rendering index (CRI) of 90 or higher (including R9 and R12 ≥ 80) can be achieved for lighting systems with baseline CRI values of 80, 85, and 90.